2003
DOI: 10.7748/ns.17.22.45.s56
|View full text |Cite
|
Sign up to set email alerts
|

Nursing management of chest drains

Abstract: This article provides an overview of the essential physiology of the respiratory system to enhance understanding of the principles of intrapleural drainage. Indications for chest drain insertion, related signs and symptoms, potential complications and nursing reponsibilities are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Most respondents would change the drainage bottle when it was broken, and half of the respondents reported that it would be changed when it was full, which was consistent with previous studies in the UK (Parkin, ), recommendations from an evidence summary (The Joanna Briggs Institute ) and some traditional reviews (Allibone, ; Crawford, ; Durai et al., ). Additionally, most respondents would change the drainage bottle when it was two‐thirds full, which has not been mentioned in previous studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most respondents would change the drainage bottle when it was broken, and half of the respondents reported that it would be changed when it was full, which was consistent with previous studies in the UK (Parkin, ), recommendations from an evidence summary (The Joanna Briggs Institute ) and some traditional reviews (Allibone, ; Crawford, ; Durai et al., ). Additionally, most respondents would change the drainage bottle when it was two‐thirds full, which has not been mentioned in previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…For example, when changing a drainage bottle, checking for an air leak or a taking a specimen, clamping for a short time was permissible (Levels of evidence: Level 4) (Chu, ; Crawford, ; Kane et al., ; Zisis et al., ), and drains for fluid drainage can be clamped or closed to control drainage rate as necessary (Ciacca et al., ). Clamping chest tubes for transporting patients was discouraged; therefore, nurses should facilitate transport of patients with a chest tube without clamping the tube, which was recommended by several traditional reviews by researchers in Egypt (Mohammed, ), the UK (Allibone, ; Durai et al., ), Australia (Crawford, ) and Greece (Zisis et al., ). An evidence summary recommended that for pneumothorax, the tubing should not be clamped if the tube is accidentally disconnected or the drainage bottle or system is broken (The Joanna Briggs Institute ) (Grades of Recommendation: Grade A), which is inconsistent with a number of traditional reviews (Crawford, ; Durai et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This paper briefly reviewed six relevant studies, but omitted several papers, including two paediatric studies. Two reviews of chest drain management were also found in the nursing literature (Gray 2000, Allibone 2003. The most recent of these did not review the literature relating to pain during removal of the drain, while the earlier paper included only three relevant studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Research has consistently shown that patients experience considerable pain during procedures performed within an acute clinical care setting and that analgesic practices vary considerably (Kinney et al 1995, Puntillo et al 2001, Puntillo et al 2002. Chest drains are inserted following a wide range of cardiothoracic surgery, trauma, postoperative complications and medical conditions to drain air, pus or fluid away from the lungs (for a review see Allibone 2003).…”
Section: Introductionmentioning
confidence: 99%